Active Teaching Strategies and Their Impact on Academic Motivation in University Students in Hybrid Learning Environments (Architecture Image Studies, 2025)
This study examines the impact of active teaching strategies on the academic motivation of university students engaged in hybrid learning environments. Using a mixed-methods approach, quantitative data were collected through standardized questionnaires, while qualitative data were obtained through semi-structured interviews. The sample included 280 students and 12 faculty members from various Ecuadorian universities. The findings indicate that methodologies such as problem-based learning, flipped classroom, and collaborative learning positively influence intrinsic motivation, self-regulated learning, and student engagement. Additionally, autonomy, meaningful peer interaction, and contextualized content emerged as key factors in fostering more dynamic and stimulating learning environments. The study concludes with practical recommendations for strengthening pedagogical design in hybrid modalities, aiming to enhance the quality and relevance of higher education learning experiences.